Identifikasi Kandungan Senyawa Kimiawi Psidium Guajava Linn. dan Anacardium Occicentale Linn. dan Efeknya terhadap Penyembuhan Luka pada Mus Musculus Linn. - Fitri Nirwana Hasibuan (Bioedunis Journal, 2022)
The aims of this research is to identify the types of chemical compounds that have the most role in wound treatment in mice (Mus musculus Linn.) using guava leaves (Psidium guajava Linn.) and cashew nuts (Anacardium occidentale Linn.). Based on TLC (Thin Layer Chromatography) analysis, the compounds contained in guava leaves and cashew leaves are flavonoids, saponins, tannins and alkaloids with a significant effect on wound treatment in mice. The amount of chemical compounds in guava leaves was 35.105 ppm, 31.508 ppm,9.400 ppm and 1.985 ppm, respectively. While in cashew leaves 42.752 ppm, 31.616 ppm, 8,001 and 1,832 ppm.